2020
DOI: 10.1088/1748-9326/ab9be5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based mapping of the wildland-urban interface to better identify human communities threatened by wildfires

Abstract: The wildland-urban interface (WUI) is the spatial manifestation of human communities coupled with vegetated ecosystems. Spatial delineation of the WUI is important for wildfire policy and management, but is typically defined according to spatial relationships between housing development and wildland vegetation without explicit consideration of fire risk. A fire risk-based definition of WUI can enable a better distribution of management investment so as to maximize social return. We present a novel methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Especially in the past two decades, changes in climate and land utilization caused by human activities have not only extended the wildfire season, but also significantly increased the severity and burned areas of wildland fires 3 . At the same time, the expansion of the wildland-urban interface (WUI) areas caused by rapid social development and sustained population growth has greatly increased the number of residents and buildings affected by wildfires, which has further aggravated the damage imparted to the human society from wildfires 4,5 . According to the data from the wildfire Redbooks published by the California Department of Forestry and Fire Protection (CAL FIRE), despite significant administrative investments in wildfire suppression and management in recent years, the property loss caused by wildfires has not been significantly reduced in California 6 .The development and implementation of proactive fire prevention policies can effectively reduce the probability of wildfire ignition, the risk of extreme fires, and the social and economic losses caused by wildfires.…”
mentioning
confidence: 99%
“…Especially in the past two decades, changes in climate and land utilization caused by human activities have not only extended the wildfire season, but also significantly increased the severity and burned areas of wildland fires 3 . At the same time, the expansion of the wildland-urban interface (WUI) areas caused by rapid social development and sustained population growth has greatly increased the number of residents and buildings affected by wildfires, which has further aggravated the damage imparted to the human society from wildfires 4,5 . According to the data from the wildfire Redbooks published by the California Department of Forestry and Fire Protection (CAL FIRE), despite significant administrative investments in wildfire suppression and management in recent years, the property loss caused by wildfires has not been significantly reduced in California 6 .The development and implementation of proactive fire prevention policies can effectively reduce the probability of wildfire ignition, the risk of extreme fires, and the social and economic losses caused by wildfires.…”
mentioning
confidence: 99%
“…Recent work has confirmed expectations that structure loss is significantly higher in the WUI than in non-WUI areas [24,25]. Although the definition and spatial delineation of the WUI varies widely [26], and may even explicitly account for wildfire probability [27], the most widely used definition and mapping rules are based on the US Federal Register, with two distinct types of WUI defined along with other map classes for varying degrees of development density and vegetation [22,23]. The difference between the two WUI types is the relative housing density and percentage cover of wildland vegetation.…”
Section: Introductionmentioning
confidence: 77%
“…Although multiple definitions of the WUI have been proposed and incorporated into policy, even explicitly accounting for fire risk [27], the underlying conceptual premise for most definitions that focus on fire is that risk and ignitions are likely to be higher where houses meet or intermingle with vegetation [23,[39][40][41][42]. Thus, the two conditions that must be present are vegetation and housing, with different classes of WUI defined based on variations in housing density and vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfire ignitions occur in WUIs around towns in southern central Chile (Miranda et al, 2020;Pozo et al, 2022) and in western-central Patagonia in Argentina, where the distribution and density of most of ignitions show a concentration in the WUIs, and diminishes toward their peripheries and less populated areas. In fact, a study in central western Patagonia showed that in a big area (337,000 ha) composed of similar vegetation types as the reported in this study, 77% of the fire ignitions occurred in the WUIs areas around towns (Godoy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%